Application of Fourier transforms and wavelet-spectrograms for identification of distortion modes of distribution networks 0,38/0,22 kV - Lezhniuk, P. D.; Miroshnyk, O. O. (Visnyk of Vinnytsia Politechnical Institute, 2015)
A comparative analysis of the use of the mathematical apparatus of Fourier and wavelet transformations for the identifi-cation of non-sinusoidal distortion modes of distribution networks 0, 38 / 0, 22 kV is conducted. The test analysis of models of signals containing different kinds of distortion is carried. The results showed the advantages of wavelet analysis to Fourier analysis, in particular through the Localization of wavelets in both time and frequency domains.